Leaving to Return: A Photographic Case Study in Western Canada (Imaginations: Journal of Cross-Cultural Image Studies, 2016)
Abstract | Adopting a collaborative framework, this paper utilizes Thomas Gardiner’s project Western Canada (2005-2010) as a catalyst for exploring the concept of a photographic community in the Canadian West. The article considers how Hollywood’s production of feature films has appropriated landscapes in Western Canada to represent American spaces. Furthermore, the article discusses how the absence of an established photographic canon in the Canadian West and the lack of institutional opportunities to assist in fostering a photographic community create particular conditions for photographic practitioners in the region. Thomas Gardiner and Kyler Zeleny’s work is discussed in relation to their multi-locational working methods. These methods include formal training and relationship building that primarily takes place outside of rural centres. The concept of a renewed photographic vision is discussed through the frame of place attachment and its relation to photographers who leave the Canadian West only to return to document once familiar spaces. In lieu of a textual conclusion, a collaboratively negotiated sequence of images between Gardiner and Zeleny serves as a dialogical exercise that is intended to draw the reader towards the imaginative work of place-making.Résumé | À travers un cadre collaboratif, cet article aborde le projet Western Canada (2005-2010) de Thomas Gardiner comme un catalyseur afin d’explorer le concept de communauté photographique dans l’Ouest canadien. Y est examiné l’impact de l’appropriation des paysages de l’Ouest du Canada par les productions filmiques hollywoodiennes en quête d’un cadre américain à rabais. À ce titre, l’article questionne également l’absence d’un canon photographique établi lié à l’Ouest canadien et la rareté des ouvertures institutionnelles apte à créer une tradition ou à tout le moins une communauté de praticiens dans cette aire géographique. Les travaux de Thomas Gardiner et de Kyler Zeleny sont ainsi examinés en lien avec leurs méthodes de « multi-localisation », méthodes qui incluent un entrainement formel et le développement d’aptitudes relationnelles, et qui prennent place surtout à l’extérieur des centres ruraux. Enfin, le concept de regard photographique renouvelé est exploré dans l’article à travers la lorgnette de l’attachement affectif au lieu et son influence sur les photographes ayant quitté le Canada dans le passé et y revenant pour mettre en scène des lieux qui leur furent familiers. À la place d’une conclusion traditionnelle, l’article offre une séquence d’images produites collectivement par Gardiner et Zeleny et qui servent en quelque sorte d’exercice dialogique afin d’attirer l’attention du lecteur sur le pouvoir d’évocation de la construction du lieu en photographie.